HU308 Mitigates Osteoarthritis by Stimulating Sox9‐Related Networks of Carbohydrate Metabolism. (27th November 2022) - Carmon, Idan; Zecharyahu, Lital; Elayyan, Jinan.; Meka, Sai R. K.; Reich, Eli; Kandel, Leonid; Bilkei‐Gorzo, Andras; Zimmer, Andreas; Mechoulam, Raphael; Kravchenko‐Balasha, Nataly; Dvir‐Ginzberg, Mona
ABSTRACT: Osteoarthritis (OA) is characterized by progressive, irreversible erosion of articular cartilage accompanied by severe pain and immobility. This study aimed to assess the effect and mechanism of action of HU308, a selective cannabinoid receptor type 2 (CB2) agonist, in preventing OA‐related joint damage. To test the assumption that HU308 could prevent OA‐related joint damage, Cnr2 null mice and wild type (WT) mice were aged to reach 20 months and analyzed for joint structural features. OA was induced in WT mice via a post‐traumatic procedure or aging, followed by HU308 local (intra‐articular) or systemic (intraperitoneal) administration, respectively. Additional analyses of time and dose courses for HU308 were carried out in human primary chondrocytes, analyzed by RNA sequencing, RT‐PCR, chromatin immunoprecipitation, and immunoblotting. Our results showed that Cnr2 null mice exhibited enhanced age‐related OA severity and synovitis compared to age‐matched WT mice. Systemic administration of HU308 to 16‐month‐old mice improved pain sensitivity and maintained joint integrity, which was consistent with the intra‐articular administration of HU308 in post‐traumatic OA mice. When assessing human chondrocytes treated with HU308, we uncovered a dose‐ and time‐related increase in ACAN and COL2A1 expression, which was preceded by increased SOX9 expression due to pCREB transcriptional activity. Finally, transcriptomic analysis of patient‐derived human chondrocytes identified patient subpopulations exhibiting HU308‐responsive trends as judged by enhanced SOX9 expression, accompanied by enriched gene networks related to carbohydrate metabolism. Collectively, the results showed that HU308 reduced trauma and age‐induced OA via CB2‐pCREB dependent activation of SOX9, contributing to augmented gene networks related to carbohydrate metabolism. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).